Vlijanie kompleksov dychatel'nych upražnenij na skorost' prochoždenija ognevych rubežej kvalificirovannymi biatlonistami v podgotovitel'nom periode - Farbey, V. V.; Zhevlakov, E. G. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The article discusses the impact of breathing exercises and technical training on the speed and effectiveness of firing by the qualified biathletes in the conditions of the preparatory period. It scientifically substantiates the use of respiratory exercise complexes in training and competitive processes that contribute to: improving the effectiveness of shooting training of qualified biathletes; stabilization of breathing before firing; stability in the shooting while lying and standing; matching breathing rhythms with the rhythm of shooting with functional shifts; it will increase the speed of passing firing lines.